How job changes affect people's lives: evidence from subjective well-being data - Chadi, Adrian; Hetschko, Clemens (Berlin, 2015)
"For representative German panel data, we document that voluntary job switching is associated with higher levels of life satisfaction, though only for some time, whereas forced job changes do not affect life satisfaction clearly. Using plant closures as an exogenous trigger of switching to a new employer, we find that job mobility turns out to be harmful for satisfaction with family life. By investigating people’s lives beyond their workplaces, our study complements research on the well-being impact of labour mobility, suggesting some positive welfare effects of flexible labour markets, but also a previously undocumented potential for negative implications."